To philosophical and legal analysis the concept of tolerance - Yuriichuk, Olena (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article deals with the concept of tolerance as one of the principles of liberal philosophical thought. Changes of paradigms in «classical» and modern philosophical and legal understanding of doctrine are analyzed. The importance of communication in the development of tolerance is highlighted, and the main approaches to understanding tolerance and its characteristic features are outlined